2017
DOI: 10.1158/1078-0432.ccr-16-2745
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin Antagonist-Based Radiotherapy of Prostate Cancer Combined with WST-11 Vascular Targeted Photodynamic Therapy

Abstract: Purpose DOTA-AR, a bombesin-antagonist peptide, has potential clinical application for targeted imaging and therapy in Gastrin Releasing Peptide receptor (GRPr) positive malignancies when conjugated with a radioisotope such as 90Y. This therapeutic potential is limited by the fast washout of the conjugates from the target tumors. WST-11 (Weizmann STeba-11 drug; a negatively charged water-soluble palladium-bacteriochlorophyll derivative, Tookad® Soluble) Vascular targeted photodynamic therapy (VTP) is a local a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…We also observed a considerable reduction in the number of CD11b + cells, including neutrophils and MDSCs in the tumor, when mice were given anti-CSF1R antibody alone or in combination with VTP ( Figure 3(f-h)). Finally, our group has previously shown that VTP obliterates the tumor vasculature in PC-3 xenografts immediately post-VTP treatment 35 and we wanted to determine if combining anti-CSF 1R with VTP therapy had any effect on the vasculature at later time points. However, we found that while the vasculature in VTPtreated tumors mostly recovered by day 10 after therapy, combining anti-CSF1R to VTP therapy had modest to little effect, which contrasted with a greater increase in vasculature in the tumors only receiving anti-CSF1R ( Supplementary Figure 7).…”
Section: Csf1r Blockade Enhances Vtp Treatment Efficacy and Improves mentioning
confidence: 99%
“…We also observed a considerable reduction in the number of CD11b + cells, including neutrophils and MDSCs in the tumor, when mice were given anti-CSF1R antibody alone or in combination with VTP ( Figure 3(f-h)). Finally, our group has previously shown that VTP obliterates the tumor vasculature in PC-3 xenografts immediately post-VTP treatment 35 and we wanted to determine if combining anti-CSF 1R with VTP therapy had any effect on the vasculature at later time points. However, we found that while the vasculature in VTPtreated tumors mostly recovered by day 10 after therapy, combining anti-CSF1R to VTP therapy had modest to little effect, which contrasted with a greater increase in vasculature in the tumors only receiving anti-CSF1R ( Supplementary Figure 7).…”
Section: Csf1r Blockade Enhances Vtp Treatment Efficacy and Improves mentioning
confidence: 99%
“…The above GRPR-antagonist was coupled with the DOTA chelator via different linkers and labeled with therapeutic radiometals, such as lutetium-177 2,28 or yttrium-90. 29 In all studies, a significant delay of tumor growth was observed in animals treated with the radiopeptide. In the present work, we have modified the same GRPR-antagonist RM26 by coupling triand tetra-aza macrocyclic chelators to its N-terminus via a PEG 2 -linker and investigated the respective 177 Lu-labeled radiopeptides for their efficacy in GRPR-targeted radiotherapy of prostate cancer in preclinical models.…”
Section: Discussionmentioning
confidence: 76%
“…Analogs of the GRPR‐antagonist [D‐Phe 6 ,Sta 13 ,Leu 14 ‐NH 2 ]bombesin(6–14) recently attracted attention as new molecular tools for TRT of prostate cancer. The above GRPR‐antagonist was coupled with the DOTA chelator via different linkers and labeled with therapeutic radiometals, such as lutetium‐177 or yttrium‐90 . In all studies, a significant delay of tumor growth was observed in animals treated with the radiopeptide.…”
Section: Discussionmentioning
confidence: 78%
“…31 Recently, a manufacturer-sponsored Phase III RCT comparing VTP with AM in 413 men with very low-risk disease has been published with 2-year follow-up data. 20 It found VTP to be safe and effective, with a 66% reduced risk of treatment failure (adjusted hazard ratio 0.34, 95% confidence interval 0.24 to 0.46) compared with AM; however, the VTP group experienced more frequent and severe side effects, although these were mostly mild and of short duration. The most common side effect was difficulty passing urine, and in all cases this resolved within 2 months of treatment.…”
Section: Vascular-targeted Photodynamic Therapymentioning
confidence: 94%
“…[17][18][19] A manufacturer-sponsored Phase III RCT of VTP versus AM in 413 men with very low-risk disease has been published recently with 2-year follow-up data. 20 This is discussed below.…”
Section: Alternatives To Conventional Therapiesmentioning
confidence: 98%